The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fgwh.2021.673168
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Access to Contraception for Youth in Urban Slums: The Challenge Initiative's Systems-Based Multi-Pronged Strategy for Youth-Friendly Cities

Abstract: Introduction: More than half of all adolescents globally live in Asia, with India having the largest adolescent population in the world at 253 million. In sub-Saharan Africa, adolescents make up the greatest proportion of the population, with 23% of the population aged 10–19. And these numbers are predicted to grow rapidly—particularly in urban areas as rural youth migrate to cities for economic opportunities. While adolescents and youth are subject to high sexual and reproductive health risks, few efforts hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Multilevel theories, such as the socioecological model, which address levels beyond the individual young person, should also be considered. While this assumes theory-based interventions are better, some programs that encompass a more iterative or quality improvement approach or that are developed in conjunction with youth or other community members may also have positive outcomes (Bose et al, 2021; Fakoya et al, 2021). Further research is needed to assess distinctions and outcomes of interventions using specific theories, such as the review of programs using PYD (Gavin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel theories, such as the socioecological model, which address levels beyond the individual young person, should also be considered. While this assumes theory-based interventions are better, some programs that encompass a more iterative or quality improvement approach or that are developed in conjunction with youth or other community members may also have positive outcomes (Bose et al, 2021; Fakoya et al, 2021). Further research is needed to assess distinctions and outcomes of interventions using specific theories, such as the review of programs using PYD (Gavin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…TCI-U also includes AYSRH interventions to address provider bias, promote youth-friendly cities, engage pharmacies and drug shops, and use other approaches that enable younger women and men to access contraceptives. 27 In addition to technical (intervention-focused) coaching on FP and AYSRH interventions, TCI provides coaching assistance to strengthen a local government's leadership, management, and coordination functions, financial management and monitoring, adaptation of interventions, and data for decision making-what TCI refers to as "essentials" for successful programming. These essentials have become an increasingly prominent focus of coaching support, based on learnings that coaching at higher levels of the health system-such as state, city, and local government area administrative levels rather than only at the facility/provider level-is required to ensure sufficient capacity to scale and potential to sustain systems level capability to maintain quality FP programming.…”
Section: Intervention Packagementioning
confidence: 99%
“…By the third quarter, local governments typically assume full leadership of the RAISE workshops to monitor their progress. 27 Through June 2021, 39 governments have graduated from full TCI support. TCI is monitoring the performance of the graduated cities by continuing to track RAISE scores and contraceptive uptake, which will inform refinements to its coaching approach and time frames of support.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Evidence suggests that youth faces high sexual and reproductive health risks and their age group is an important social determinant of health [ 7 , 24 ]. A study comparing contraceptive use in adolescent girls (ages 15–19 years) and adult women (ages 20–34) in 103 low- and middle-income countries between 2000 and 2017 found that adolescent girls continue to fall behind adult women in contraceptive use [ 25 ].…”
Section: Introductionmentioning
confidence: 99%